Perkecambahan Benih Kacang Panjang Ungu pada Berbagai Media yang Berbeda - Manurung, Adinda Nurul Huda (Jurnal Pertanian Presisi (Journal of Precision Agriculture), 2019)
Indonesia is one of the centers for planting long beans that have extensive genetic diversity. Purple long bean is one of the new long bean varieties. There has not been much research on this purple-bean long bean seed. Information about the addition of purple long bean seeds is still very limited. One of the important things in germination is the selection of appropriate media. Germination media play an important role in helping to accelerate seed germination and each type of seed plant has different tendencies about media suitable for germination. The purpose of this study was to determine the best germination media for purple-bean long beans.This research was conducted at F6 Campus Gunadarma University located at Depok (Â±115 m above sea level) on January 2019. The treatment was arranged in Completely Randomized Design with ten replications. The treatment was germination media, i.e organic fertilizer (M1), sand (M2), and organic fertilizer : sand (1:1) (M3). The result showed that germination media had significant effect toward sproud height, number of leaves, leaf area, root lenght and fresh weight sproud. this study concluded that organic fertilizer is the best media for germination of purple long beans.Keywords : biomassa, organic, vegetatif growth